A new species of the genus Humphaplotropis from China (Orthoptera: Pamphagidae, Pamphaginae) - Shi, Jian-Ping; Yin, Zhan; Dai, Li (Zootaxa, 2018)
A new species of the genus Humphaplotropis Xiao et al, 2013, i.e. Humphaplotropis tongbaishanensis sp. nov. is described from Henan province, China in this paper. The new species is allied Humphaplotropis xiai Zhi, Shi & Dai, 2015, but differs from latter by tegmina of male short, not reaching the hind margin of 1st abdominal tergite; base of cercus not narrow in male; epiphallus with disperse spikes, ancorae broad, both posterior projections shorter than median projection; length of subgenital plate larger than width in female and Krauss` organ of female with 20 keels. The genus Humphaplotropis Xiao et al, 2013 is a valid genus and not a synonym of Haplotropis Saussure, 1888. Type specimens are deposited in Shanghai Entomological Museum, C.A.S., Shanghai China.